Z-contrast Imaging in an Aberration-corrected Scanning Transmission Electron Microscope. - Pennycook, S; Rafferty, B; Nellist, P (2000)
We show that in the limit of a large objective (probe-forming) aperture, relevant to a spherical aberration corrected microscope, the Z-contrast image of a zone-axis crystal becomes an image of the 1s Bloch states. The limiting resolution is therefore the width of the Bloch states, which may be greater than that of the free probe. Nevertheless, enormous gains in image quality are expected from the improved contrast and signal-to-noise ratio. We present an analytical channeling model for the thickness dependence of the Z-contrast image in a zone-axis crystal, and show that, at large thicknesses, columnar intensities become proportional to the mean square atomic number, Z(2).